2020
DOI: 10.1098/rspb.2020.0895
|View full text |Cite
|
Sign up to set email alerts
|

Testing the greater male variability phenomenon: male mountain chickadees exhibit larger variation in reversal learning performance compared with females

Abstract: The greater male variability phenomenon predicts that males exhibit larger ranges of variation in cognitive performance compared with females; however, support for this pattern has come exclusively from studies of humans and lacks mechanistic explanation. Furthermore, the vast majority of the literature assessing sex differences in cognition is based on studies of humans and a few other mammals. In order to elucidate the underpinnings of cognitive variation and the potential for fitness consequences, we must i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
(100 reference statements)
0
21
0
Order By: Relevance
“…Our data supports the interpretation that females exhibit greater response demands (and consequently slower performance) than males in the reversal phase. This adds to a growing literature on sex differences in reversal learning (Aarde et al, 2020;Bissonette et al, 2012;Branch et al, 2020;LaClair & Lacreuse, 2016).…”
Section: Sex Differencesmentioning
confidence: 73%
“…Our data supports the interpretation that females exhibit greater response demands (and consequently slower performance) than males in the reversal phase. This adds to a growing literature on sex differences in reversal learning (Aarde et al, 2020;Bissonette et al, 2012;Branch et al, 2020;LaClair & Lacreuse, 2016).…”
Section: Sex Differencesmentioning
confidence: 73%
“…Differences in variance thus do not appear to be a mechanical consequence of differences in mean, and instead may reflect a distinct phenomenon known as the greater male variability hypothesis. This hypothesis states that males are more variable than females across a variety of psychological and physical characteristics (Ellis, 1894) and is widely supported by a range of human (e.g., Johnson et al, 2008;Ju et al, 2015;Karwowski et al, 2016;Lehre et al, 2009;Wierenga et al, 2019) and animal (e.g., Branch et al, 2020;DeCasien et al, 2020) studies.…”
Section: Sex Differences In Variancementioning
confidence: 99%
“…Our findings appeared to be robust to differences in sex and motivation as we found no effects of these factors on performance on the spatial task, movement speed or straightness in our study. Previous research has found distinct sex differences in spatial cognitive ability linked to larger home ranges [ 67 ], more complex habitats [ 68 ] or differential breeding biology [ 69 ] for one particular sex, although see [ 70 ]. Pheasants display pronounced sex differences in movement and space use, exhibiting sexual segregation between November and February [ 35 ] and with females typically dispersing further than males [ 71 ].…”
Section: Discussionmentioning
confidence: 99%